2020
DOI: 10.1177/2309499020905134
|View full text |Cite
|
Sign up to set email alerts
|

Urinary retention after total joint arthroplasty of hip and knee: Systematic review

Abstract: Purpose: Postoperative urinary retention (POUR) is a common complication after total joint arthroplasties (TJAs). The POUR is managed with urinary catheterization, which is associated with a risk of urinary tract infection and subsequent periprosthetic joint infection. The purpose of this review was to afford a comprehensive understanding of POUR and its management. Methods: We identified 15 original articles concerning POUR after TJA, which were published from January 2010 to February 2019. The diagnostic met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…In addition, a recent systematic review of 6397 TJA patients concluded that indwelling catheters should only be used in cases of persistent POUR despite repeated intermittent catheterization. If an indwelling catheter was inevitably used, it should be removed within 48 hours [ 21 ]. While the evidence suggests that indwelling catheters pose significant risks to TJA patients, little has been done to stratify risk for urinary catheterization based on a patient’s preoperative profile.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent systematic review of 6397 TJA patients concluded that indwelling catheters should only be used in cases of persistent POUR despite repeated intermittent catheterization. If an indwelling catheter was inevitably used, it should be removed within 48 hours [ 21 ]. While the evidence suggests that indwelling catheters pose significant risks to TJA patients, little has been done to stratify risk for urinary catheterization based on a patient’s preoperative profile.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other surgery, total arthroplasties carried a grater incidence of postoperative urinary retention in human patients, but the actual bladder capacity was estimated by ultrasound. 39 Using an ultrasound, postoperative urinary retention was detected in 5.9% of dogs after extradural anaesthesia. 11 Considering that dogs were cage rested for a variable amount of time, especially at centre A, and that only 3.2% of dogs needed postoperative intervention to empty the urinary bladder, it is possible that the bladder capacity was not completely full after 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence against the routine use of catheterization aims to avoid the risk of urinary retention and infection [31][32][33]. Postoperative urinary retention is a common complication after the total joint arthroplasty and the incidence ranged from 4.1-46.3% [34]. Patients with a history of urinary retention and high volume of uid tend to experience urinary retention and infection postoperatively.…”
Section: Discussionmentioning
confidence: 99%